Exploring the institutional perspective on international business expansion: Towards a more detailed conceptual framework - Richard L. Lynch; Zhongqi Jin (Journal of Innovation & Knowledge (JIK), 2016)
While the general principles of the Institutional Perspective have been widely accepted, there has been only limited consideration to the present time of their in-depth application to the strategies of individual firms engaged in international business. The paper argues that companies engaged in such activities will find that there is a significant gap in precisely what aspects of the formal and informal institutional perspectives need to be identified and assessed for international expansion. The purpose of this paper is to develop a theoretical paradigm that allows organizations not only to compare different countries with regard to their potential for international business expansion from the perspective of Institutional Theory but also drawing on theories of International Business Strategy where relevant. The theoretical framework assumes that such organizations are engaged in analyzing the institutional arrangements and resources of their home and possible host countries. The paper then develops a conceptual framework that identifies five major components, namely people, power, performance, pathways to international expansion, and productivity, the latter being defined in terms of knowledge and innovation. It explores each of these areas in more depth with the aim of adding a more detailed structure to elements of Institutional Theory relevant to international business expansion.
Keywords: 650; International business; Institutional theory; Country comparison